The Use of TADs in the Mandibular Arch to Prevent Proclination of the Lower Incisors during the Use of the Mini Scope Herbst Appliance - Domenico Aiello; Angelo Finamore; Andrea Scribante; Michele Mario Figliuzzi; Sergio Paduano (Hindawi Limited, 2022)
Class II malocclusions are the most frequent within the Italian population. Normally, these malocclusions are caused by a reduction in a mandibular component whose functional stimulus is still very much cause for debate. The negative effect of all types of Class II functional appliances is in the proclination of the lower incisors, which, in subjects whose incisors are already labially inclined, must be checked at all times to avoid serious consequences to these elements. In this case study, a girl aged 14 years and 5 months presented with Class II malocclusion, 2nd division with a convex profile and a visibly retruded chin. The lower incisors presented a marked proclination (−1/Go-Gn ini = 107.7°) in a brachyfacial patient. To avoid further inclination of the lower incisors a Herbst appliance was mounted in two separate sittings. The first part of the appliance including the tubes was mounted to the upper jaw allowing the vestibularisation of the upper incisors in order to increase the overjet. Once this was obtained the lower part of the appliance was mounted together with the telescopic arms associated with two temporary anchorage devices (TADs) in positions 36-37 and 46-47, and an anterior section 33-43 with distal loop to which two double metallic ligatures were anchored at the TADs to contrast the negative effect of the appliance. At the end of the first functional phase, the treatment was refined using MBK fixed therapy to finish the case. The orthodontic therapy led to a visible improvement of the profile and the achievement of a first-class dental-skeletal result on both sides. From the cephalometric evaluation carried out immediately after the Herbst appliance treatment at time T1 and at the end of the orthodontic therapy T2 it was possible to verify a slight increase in the inclination of the lower incisors (−1/Go-Gn fin = 108°). In conclusion, it can be said that the use of the skeletal anchorage avoided, in this case, the proclination effect in the lower incisors due to the use of a Herbst appliance.